2019
DOI: 10.1002/jcpy.1094
|View full text |Cite
|
Sign up to set email alerts
|

Children's Understanding of the Instrumental Value of Products and Brands

Abstract: Gelman and Echelbarger (2019—this issue) provide a valuable discussion about children's understanding of the inferred or nonobvious features of objects, which has implications for how children value products. We further this conversation by examining how children value products and brands as a means for meeting important goals, which we refer to as instrumental valuation. Specifically, we examine developmental trends in instrumental valuation for three goals—self‐concept development, self‐presentation, and hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Children may mentally weigh the value of the character's image against the value of the object's quality (Danovitch & Mills, 2014). Perceived object value is sometimes determined by more than object cleanliness or functionality – rather, objects sometimes carry unseen value resulting from history, ownership, self‐presentation or self‐concept expression (Gelman & Echelbarger, 2019; John & Chaplin, 2019) For example, Gelman and Davidson (2016) found that children preferred damaged to undamaged versions of the same object when the damaged object carried sentimental value. Similarly, children may value the image of, or association with, the popular character so much that they are sometimes willing to overlook the damage to the object.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children may mentally weigh the value of the character's image against the value of the object's quality (Danovitch & Mills, 2014). Perceived object value is sometimes determined by more than object cleanliness or functionality – rather, objects sometimes carry unseen value resulting from history, ownership, self‐presentation or self‐concept expression (Gelman & Echelbarger, 2019; John & Chaplin, 2019) For example, Gelman and Davidson (2016) found that children preferred damaged to undamaged versions of the same object when the damaged object carried sentimental value. Similarly, children may value the image of, or association with, the popular character so much that they are sometimes willing to overlook the damage to the object.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies did not ask children to consider the intended use of the objects (rather, only their preferences have been explored), and thus, children may have focused more on the character's image than the object's functionality. Children may place greater emphasis on the characters' image in these situations, for example because the character's image may add unseen value to the object related to affiliation with the character, self‐presentation goals or self‐concept expression (Gelman & Echelbarger, 2019; John & Chaplin, 2019), or children may be drawn to the object as a result of parasocial relationships (i.e., one‐sided emotional relationships) individuals form with media characters (Horton & Wohl, 1956; Kotler et al, 2012). This study investigated whether increasing the salience of object quality would influence children's choices by asking children to select one of the objects (damaged or undamaged) to use for its intended purpose (i.e., using a bucket to carry several small items).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some studies examine children's consumer development from the point of sales promotions (Boland et al, 2012), money perceptions, money use, or financial attitude development (Drever et al, 2015; Fiates et al, 2008; Friedline, 2015; Otto & Webley, 2016; Ribeiro et al, 2018). Children's consumer development from the point of value perception is also examined, such as children's value perceptions in decision‐making (Williams et al, 2016), their valuation of objects for meeting important goals (John & Chaplin, 2019), and assessment of products' perceptual attributes (Wang & Li, 2019). Children's understanding of new marketing tactics (Freeman & Shapiro, 2014), social networking sites (Lawlor et al, 2016), and their understanding and usage of different shopping channels (mall, Internet) (Lueg et al, 2006) and online shopping (Thaichon, 2017) are also investigated with a developmental lens.…”
Section: Key Research Areasmentioning
confidence: 99%
“…Marketing research that addresses learning in children and adolescents has traditionally been part of the domain of consumer socialization (Brée, 1993;Moschis and Churchill, 1978;Roedder John, 2001;Ward, 1974). The past decade has also seen an increasing body of work that focuses more specifically on the social dimension of learning, notably the development of consumer culture among young people (Gelman and Echelbarger, 2019;Hémar-Nicolas and Rodhain, 2017;Nairn and Spotswood, 2015;Roedder John and Chaplin, 2019). In this article, we draw upon these two complementary approaches in order to understand the normative pressure from peers with respect to consumption in schools.…”
Section: Peer-influenced Consumption In Schools and The Place Of Sb I...mentioning
confidence: 99%
“…Thus, a particular brand of clothing may be soughtafter for its ability to attract peer approval. However, this brand-related "quality" may be perceived as irrelevant if a child is not particularly interested in being a member of a specific group (Nairn and Spotswood, 2015;Roedder John and Chaplin, 2019). Therefore, susceptibility to peer influence, which can be equally informational as normative, 3 impacts the importance given to peer pressure regarding consumption (Auty and Elliott, 2001;Benmoyal Bouzaglo and Guiot, 2013;Lachance et al, 2003).…”
Section: Individual Factors Relevant To Understanding Young People's ...mentioning
confidence: 99%